Marcus Stevenson: capstone - Stevenson, Marcus, artist (Colorado State University. Libraries, 2016)
The artist's statement: My approach to making is to adapt, collage, and re-contextualize imagery and objects which helped to form my worldview. Using woodworking techniques, I combine recycled objects, marbles, electric motors, found and bought hardware, and all kinds of mechanical arrangements to create tension between tradition and the novelty. For example, my 'Lectric Tricycle Drones consist of a simple motor circuit in combination with wheels and a monorail system. The name of the work evokes the new wave of hi-tech, autonomous vehicles, but the wooden construction, finish quality, and lack of utilitarian purpose hearken back to a time where toys and games were less about bells and whistles, and more about deriving enjoyment from simplicity. I feel it is important to make art which is accessible in its visual vocabulary, and also an honest translation of my worldview. Since it's hard or even impossible to encapsulate an entire worldview into a single object, I aim to parse aspects of my worldview and human experience into the objects I make. Toys seem to offer the next generation an instance of the values of previous generations. I think we behave as if the creation of new ideas categorically invalidates old ideas, and this is often to our detriment as a society. Ultimately, I have to admit that my foremost goal as an artist is to entertain, and then to sneak what little wisdom I have through the door in the process. At the end of the day, I'm still just a kid who wants to have fun, and share it, too.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: sculpture